2020
DOI: 10.1186/s12871-020-00969-0
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy compared ultrasound-guided continuous transverse abdominis plane block with epidural analgesia following abdominal surgery: a systematic review and meta-analysis of randomized controlled trials

Chaosheng Qin,
Yuanming Liu,
Jijun Xiong
et al.

Abstract: Background: This review and meta-analysis aims to evaluate the analgesic efficacy of continuous transversus abdominis plane (TAP) block compared with epidural analgesia (EA) in adults after abdominal surgery. Methods: The databases PubMed, Embase and Cochrane Central Register were searched from inception to June 2019 for all available randomized controlled trials (RCTs) that evaluated the analgesic efficacy of continuous TAP block compared with EA after abdominal surgery. The weighted mean differences (WMDs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…Meanwhile, it can inhibit abdominal visceral pain, which is beneficial to relieving stress response and stabilize intraoperative blood pressure and heart rate. TAPB anesthesia guided by ultrasound can improve the stress response and immune function of patients undergoing laparoscopic colon cancer surgery [ 15 , 16 ]. The results of this study are basically consistent with the conclusion.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, it can inhibit abdominal visceral pain, which is beneficial to relieving stress response and stabilize intraoperative blood pressure and heart rate. TAPB anesthesia guided by ultrasound can improve the stress response and immune function of patients undergoing laparoscopic colon cancer surgery [ 15 , 16 ]. The results of this study are basically consistent with the conclusion.…”
Section: Related Workmentioning
confidence: 99%
“…The inclusion of regional anesthesia in perioperative pain control regimens has been shown to be superior to opioid or non-opioid analgesic modalities alone (4)(5)(6). However, some studies have shown ethnic-based disparities in the use of regional anesthesia (1,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reviews have been conducted on postoperative pain management, some of which include ultrasound-guided transversus abdominis pain block, with some exploring the best anesthetic technique [ 25 , 26 , 27 , 28 ] and abdominal surgeries [ 3 , 29 , 30 , 31 , 32 , 33 , 34 ]. Other reviews focused on specific conditions, such as colorectal surgery [ 35 , 36 ], wound infiltration [ 33 , 37 ], caesarean delivery [ 38 ], bariatric surgery [ 39 , 40 ], lower abdominal incisions [ 16 ], breast reconstruction [ 41 ], and minimally invasive surgery [ 42 ].…”
Section: Introductionmentioning
confidence: 99%